La sexualidad en adolescentes con trastorno del espectro autista. - Chacha Simba, Shirley Sharlothe (2025)
Sexuality in autism spectrum disorder (ASD) establishes a little explored area; this research had as objective to analyze the sexuality of this population, taking account dimensions like orientation, identity, and sexual experiences. This research was realized through a quantitative approach, descriptive level, and a bibliographic design. It was initially shaped by 627 scientific articles, which were extracted from databases like Scopus, Web of Science, Pub Med, and Springer, published between 2015 and 2025, which were filtered according to standards of inclusion and exclusion that itemize the PRISMA methodology; and they were submitted to a methodological quality evaluation where Critical Review Form- Quantitative Studies (CRF- QS) instrument was applied, counting with 20 articles with variables of interest. The main results showed that teenagers with ASD feel desire and sexual interest just like the other ones who don't have autism, but the first group faces difficulties to establish emotional relationships, understand social norms, and express their sexuality appropriately; besides, parents and carers avoid these themes or they don't know suitable strategies to talk about it, increasing vulnerability with this population. In conclusion, we can recognize that sexuality with this group is complex and diverse, far from social stereotypes, and the behaviors considered "inappropriate", they mainly respond according to environment which doesn't offer required tools to better development; for that reason, is necessary to apply intervention strategies adapted to their needs and guarantee their life quality.